Dressed as in a Painting : Women and British Aestheticism in an Age of Reform - Wahl, Kimberly (Book collections on Project MUSE., 2013)
In Dressed as in a Painting, Kimberly Wahl provides a lucid exploration of the interrelations between fashion, art, and Aestheticism during the latter half of the nineteenth century. Although artistic forms of dress have been the subject of short studies before, no book has focused exclusively on Aesthetic dress and its various expressions in the visual cultures of Victorian Britain. More important, no book has attempted to investigate the gap between the material facts of artistic clothing as it was embodied on the wearer, and its presence as an idealized sartorial trope in the visual and tex.